Electric drive axle systems in new energy vehicles - Liu, Yingshuai; Tan, Jingsong; Shi, Shuo; Tan, Jianwei (Frontiers in Mechanical Engineering, 2026)
This study set out to benchmark how far recent advances in motor–gearbox integration, thermal management and control algorithms could jointly raise the efficiency of electric-drive axles for new-energy vehicles. The different schools of thought regarding the integration of electric motors and gearboxes were discussed and distilled into a single framework before quantitative analysis began. A 2020–2025 literature synthesis then revealed that, relative to single-speed hardware, two-speed gearboxes increased motorway-cycle motor efficiency by 5%–7% without raising urban energy demand; oil–water hybrid cooling restricted the motor-and-gearbox temperature band to ±3 °C and lifted heat-transfer efficiency by 25%; while model-predictive control with road-slope preview curbed hilly-route consumption by 8%–10% and cut torque-response latency by ∼30%. CFRP housings, titanium-matrix rotors and topology-optimised planetary trains further lowered axle mass by 15%–20% and gear-mesh noise by 8–10 dB, offsetting the added mechanical complexity. Collectively, these refinements yielded a ∼10% net energy saving and 30% faster transient response, proving that concurrent hardware–thermal–software optimisation extended vehicle range without battery upsizing. Standardised extreme-temperature durability protocols, low-cost stamped micro-channel coolers and digital-twin-based predictive maintenance were identified as the next steps to accelerate commercial deployment.